Efficacy of BREATHOX® Device Inhalation on Acute Symptoms Associated with COVID-19 (BREATH Study): A Randomized Pilot Clinical Trial - Tanni, Suzana [UNESP]; Wehrmeister, Fernando; Prudente, Robson [UNESP]; Damatto, Felipe [UNESP]; Breda Neto, Carlos [UNESP]; Oliveira, Leiliane [UNESP]; Pagan, Luana [UNESP]; Gatto, Mariana [UNESP]; Vieira, Letícia [UNESP]; Coelho, Liana [UNESP]; Rezende, Diane [UNESP]; Machado, Luiz [UNESP]; et al. (MDPI, 2023)
(1) Background: A high concentration of sodium chloride on in vitro cell culture leads to reduced SARS-CoV-2 replication. Therefore, our aim was to evaluate the effects of inhaling hypertonic NaCl particles (BREATHOX®) on the duration of COVID-19-induced acute symptoms. (2) Methods: A prospective, open label, randomized, standard of care-controlled group (SOC) pilot trial compared inhaled oral and nasal administered BREATHOX® (2.0 mg NaCl, particles size between 1–10 μm), with five or ten inhalations per day for ten days. The primary endpoint was the time to resolve COVID-19-related symptoms. Safety outcomes included adverse clinical and laboratory events. (3) Results: A total of 101 individuals were screened and 98 were randomly assigned to BREATHOX® ten sessions per day (Group 1; 33 patients), BREATHOX® five sessions per day (Group 2; 32 patients), or SOC (33 patients), and followed up for 28 days. There was an association with cough frequency after 10 days BREATHOX® compared to SOC [Group 1: hazard ratio (HR) 2.01, 95% confidence interval (CI) 1.06–3.81; Group 2: HR 2.17, 95% CI 1.17–4.04]. No differences between the groups for the reported symptoms’ resolution time were seen after 28 days. After combining both BREATHOX® groups, the period to cough resolution 10 days after randomization was significantly lower than in SOC (HR 2.10, 95% CI 1.20–3.67). An adverse event occurred in 30% of Group 1, 36% of Group 2, and 9% in SOC individuals. One patient from SOC had a serious adverse event. Nasal burning, sore or itchy nose, and dry mouth were considered related to BREATHOX® use and resolved after stopping inhalations. (4) Conclusion: BREATHOX® inhalation is safe and may be effective in reducing the duration of COVID-19-induced coughing.
Keywords: hypertonic saline; mild COVID-19; SARS-CoV-2; treatment